Analisis Faktor-Faktor yang Mempengaruhi Nilai Tukar Petani Tanaman Pangan di Provinsi Jawa Barat Tahun 2008-2021 - Adila Nurul Apipah (Bandung Conference Series: Economics Studies, 2023)
Abstract. Exchange Value of Farmers (EVF) is one measure in determining the welfare of farmers. EVT can also show exchenge rate for the cost of products and agricultural goods and service consumend. The determination of the level of welfare of farmer comes from calculating the percentage of value paid by farmers. If the farmer’s exchange rate is more than 100, it means that the farmer’s welfare level is goog. This study aims to analyzethe Factors Affecting the Exchange Rate of Food Crop Farmers in West Java 2008-2021. In this study the variables used are productivity, land area and inflation. The data used is time series data with an ordinary least square (OLS) approach using Eviwers. The research results show that the factors influencing the Exchange Value of agricultural commodity farmers in West Java from 2008 to 2021 are simultaneously affected by productivity, land area, and inflation. However, partially, the inflation variable does not have a significant effect on the exchange rate of food crop farmers. Meanwhile, in West Java partially, productivity variables and land area influence the exchange value of agricultural commodity farmers. Keywords: farmer exchange rate, food crops, land area, productivity, inflation Abstrak. Nilai Tukar Petani (NTP) menjadi salah satu ukuran saat ditentukannya kesejahteraan petani. NTP juga mampu menunjukan nilai tukar atas biaya produksi produk pertanian dan barang serta jasa pertanian yang dikonsumsi. Penentuan tingkat kesejahteraan petani bersumber dari perhitungan persentase nilai yang dibayarkan oleh petani. Jika nilai tukar petani melebihi angka 100, menandakan bahwa tingkat kesejahteraan petani berada pada kondisi yang baik. Penelitian ini mempunyai tujuan guna menganalisis Faktor- Faktor Yang Mempengaruhi Nilai Tukar Petani Tanaman Pangan di Jawa Barat 2008-2021. Pada penelitian ini variabel yang dimanfaatkan yakni produktivitas, luas lahan dan inflasi. Data yang digunakan yakni data time series dan dianalisis dengan memanfaatkan pendekatan ordinary least square (OLS) serta menggunakan perangkat lunak Eviews. Hasil penelitian menunjukkan faktor-faktor yang memberikan pengaruh pada Nilai Tukar Petani tanaman pangan di Jawa Barat tahun 2008-2021 terpengaruhi secara simultan oleh produktivitas, luas lahan dan inflasi. Namun secara parsial, variabel inflasi tidak memberikan pengaruh yang signifikan kepada nilai tukar petani tanaman pangan. Sementara itu, di Jawa Barat secara parsial variabel produktivitas dan luas lahan mempengaruhi nilai tukar petani komoditas tanaman pangan.